A study of liver function in females with toxic goiter by using 131I Rose Bengal - Al-Shami, Adeeb Abass (Al Mustansiriyah Journal of Pharmaceutical Sciences, 2008)
26 consecutive female patients with goiter their age range between 22 – 65 years. Nodular forms were 10 patients, diffuse goiter were16 patients, euthyroid form were 6 patients, with sign of thyrotoxicosis (severe thyrotoxicosis 11 patients, moderate 9 patients). Sensitive test, Rose Bengal conjugated with 131I was used for evaluation the absorption& excretion by liver cells and intrahepatic blood circulation. The results showed increase blood flow, liver accumulation of isotope in 25% of the patients and in 45-50% of patients were normal. The excretion of conjugated Rose Bengal with 131I shows severe suppression of liver function in 2 cases. In this study we found an increasing the maximum accumulation time of isotope 131I in the liver, both in severe & moderate thyrotoxicosis.